Trade, exchange rate, and growth in sub-Saharan Africa - Azam, Jean-Paul (Cambridge University Press, 2007)
In this sophisticated yet accessible analysis of the open economies of Sub-Saharan Africa, Jean-Paul Azam analyses international trade, exchange rate issues, and longer-term growth, taking due account of the distinctive features of African economies. In particular, he examines the informal as well as the formal institutional frameworks which prevail in different African countries and which affect their macroeconomic behaviour. Key issues explored include tariffs and quotas, membership of the CFA Zone, and currency convertibility or inconvertibility, as well as smuggling, corruption, parallel markets in goods and currencies, ethnic diversity and redistribution. Case studies of important macroeconomic events are used to establish basic stylized facts from which the theory emerges, and special attention is paid to the consequences of macroeconomic events for the poor, via the food market or traditional redistribution mechanisms